ARTIFICIAL INSEMINATION PROTOCOLS IN CATTLE: TECHNIQUES TO OPTIMIZE CONCEPTION RATES - Gomes, Leandro Giroux; Cavalcante, Átila Bonfim Ferreira; de Souza, Ana Edvirgens Vasconcelos; Martins, Jessica Saldanha; Comes, Henrique Leite França; Rizzi, Otávio Silveira (Seven Editora, 2026)
Artificial insemination (AI), and especially fixed-time artificial insemination (FTAI), have become established as central biotechnologies to enhance reproductive efficiency and accelerate genetic gain in cattle production systems by reducing dependence on estrus detection. Despite their widespread adoption, reproductive performance achieved under field conditions remains dependent on the interaction between the hormonal protocol, the physiological and metabolic status of the females, and the operational quality of the service. This narrative review synthesizes recent evidence (2021–2025) on estrous cycle synchronization strategies based on progesterone (P4), estrogens, and luteolysis with prostaglandin F2α (PGF2α), highlighting the importance of maintaining adequate P4 concentrations during dominant follicle development for oocyte competence and subsequent luteal functionality. Additionally, the use of equine chorionic gonadotropin (eCG) as a supportive tool in cows with low body condition and higher probability of anestrus is discussed, as well as the impact of inseminator training and semen handling (storage, thawing, and intrauterine deposition) on conception rates. Finally, emerging perspectives related to omics sciences are addressed, with emphasis on circulating microRNAs as potential biomarkers for predicting pregnancy success and enabling early diagnosis, with implications for reducing the interval between services and optimizing system profitability. It is concluded that maximizing conception rates in AI/FTAI programs depends on an integrated approach combining protocol design, nutritional management, and technical excellence, in addition to the critical and gradual incorporation of higher-resolution diagnostic tools.